2022
DOI: 10.1038/s41598-022-24999-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic conditions induce rapid cell dysfunction-promoting transcriptional alterations in human aortic endothelial cells

Abstract: Hyperglycemia is a major risk factor in the development of diabetic complications and promotes vascular complications through dysregulation of endothelial cell function. Various mechanisms have been proposed for endothelial cell dysregulation but the early transcriptomic alterations of endothelial cells under hyperglycemic conditions are not well documented. Here we use deep time-series RNA-seq profiling of human aortic endothelial cells (HAECs) following exposure to normal (NG) and high glucose (HG) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…We demonstrated that endothelial cell replicative senescence is characterized by an increased burden of cytoplasmic nucleic acids and that a high glucose treatment can induce some features of senescence, such as DNA damage, telomere attrition, increased proinflammatory cytokine release, and increased burden of cytoplasmic misplaced nucleic acids, in young/functional endothelial cells. Our experimental conditions, a longtime cell exposure to HG (7 days), could mirror a chronic hyperglycemic condition more than an acute glucose-induced stress (i.e., 24-h HG) [ 30 ]. In this regard, we previously showed that such exposure was sufficient to induce senescence and the SASP in endothelial cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that endothelial cell replicative senescence is characterized by an increased burden of cytoplasmic nucleic acids and that a high glucose treatment can induce some features of senescence, such as DNA damage, telomere attrition, increased proinflammatory cytokine release, and increased burden of cytoplasmic misplaced nucleic acids, in young/functional endothelial cells. Our experimental conditions, a longtime cell exposure to HG (7 days), could mirror a chronic hyperglycemic condition more than an acute glucose-induced stress (i.e., 24-h HG) [ 30 ]. In this regard, we previously showed that such exposure was sufficient to induce senescence and the SASP in endothelial cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This overproduction of AGEs is associated with an increased endothelial cell permeability, inhibition of endothelial NO synthase (eNOS) activity, and enhanced detrimental alterations of DNA and proteins leading to cell damage [ 15 ]. Hyperglycemia rapidly activates cellular proliferation in endothelial cells through the stimulation of different proinflammatory and growth factors including the hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) family ligand–receptor, Erb-B2 Receptor Tyrosine Kinase 4 (ErbB4), insulin-like growth factor (IGF-1), bone morphogenetic protein (BMP), nuclear factor of activated T-cells (NFAT), signal transducer and activator of transcription 3 (STAT3), nuclear factor-kappaB (NF-κB), p70S6K and hypoxia-inducible factor-1alpha (HIF-1α) signaling pathways [ 17 ]. Moreover, hyperglycemia increases the expression of membrane cofactor protein-1 (MCP-1) and NLR family pyrin domain containing 3 inflammasome (NLPR3) and promotes mitochondrial oxidative stress and apoptosis.…”
Section: Cardiometabolic Alterations and Endothelial Dysfunctionmentioning
confidence: 99%
“…Hyperglycemic conditions in vivo are simulated in vitro by culturing the cells in HG conditions to study the effects of hyperglycemia. HG culture conditions have been shown to cause rapid cellular dysfunction by promoting transcriptional changes[ 13 ]. Some of the essential mechanisms involved therein include the formation of advanced glycation products (AGEs), PKC activation, mTOR/Akt dysregulation, etc , that lead to elevated reactive oxygen species (ROS) stress, increased pro-inflammatory cytokines production, growth factors, abnormally high gas transmitters, altered cell bioenergetics, etc.…”
Section: Hg Culture- and Hyperglycemia-induced Signalingmentioning
confidence: 99%
“…They supported their findings by treating the cells with oxidizing agents and silencing PKC-β in the cells to inhibit their adipogenic differentiation. In a subsequent study, culture of human aortic endothelial cells in HG was reported to cause significant pathway changes during the first 4 h, with distinct clusters of genes showing altered transcriptional profiles unique to HG conditions[ 13 ]. Temporal co-expression and causal network analysis showed a relationship between type 2 diabetes mellitus and activation of growth factor signaling pathways, including signal transducer and activator of transcription 3 and nuclear factor-kappa B.…”
Section: Hg Culture- and Hyperglycemia-induced Signalingmentioning
confidence: 99%